PELATIHAN KETERAMPILAN PEMBUATAN PRODUK HOME INDUSTRY PADA KARANG TARUNA DESA SENYIUR - Mizriaty, Alfina; Yahdi (Universitas Mataram, 2024)
Senyiur Village is a village located in Jerowaru District, East Lombok Regency, West Nusa Tenggara with a population of 4359 people. Most of the village area is rice fields and plantations so that the main livelihood of the population is in the agricultural and plantation sectors (21.61%). It is known that 32.9% of the population does not have a job. Villagers really want to start a business, but the skills they have are relatively low. The aim of this activity is to provide the youth of Senyiur Village Karang Taruna with skills in making home industry products based on hygiene products such as laundry perfume, softener, dishwashing soap, and so on. This activity was attended by 27 Karang Taruna youth. Supervised by 7 field assistants and carried out in three stages. The first stage is a presentation and discussion session, the second stage is training in making home industry products and the third stage is evaluation activities. The result of this activity is the creation of various home industry products, the growth of participants' interest and skills in making home industry products. The development of the creative economy in Senyiur Village, which is a small village where the majority of the population's livelihood is farmers and livestock breeders, is expected to provide new options for young people to become entrepreneurs. Moreover, in the current digital era, consumers have a tendency to search for and purchase various needs through digital channels such as websites, mobile applications and social media. This will be the main supporting capacity in the future if you are interested in entrepreneurship in the home industry sector. Community-based home industry training in Senyiur Village can foster interest and skills in making a variety of home industry products.